Essential Oils Composition from Different Parts of Artemisia kermanensis Podl. - Kazemi, M.; Yasrebifar, Z. (Asian Journal of Chemistry, 2011)
Chemical composition of essential oils from stem, leaf and flower of Artemisia kermanensis Podl. were analyzed by gas chromatography and gas chromatography-mass spectroscopy methods. Among of 40 identified compounds, camphor (20.3 %) and 1,8-cineole (11.2 %) found the main components of stem whereas the major constituents of leaf was selin-11-en-4-a-ol (18.6 %) besides, the main compounds of flower oil were isoborneol (17.1 %) and santolina alcohol (10.6 %).